Reflex Human Papillomavirus Test Results as an Option for the Management of Korean Women With Atypical Squamous Cells Cannot Exclude High-Grade Squamous Intraepithelial Lesion. (11th May 2015) - Ryu, Ki-Jin; Lee, Sanghoon; Min, Kyung-Jin; Kim, Jae Won; Hong, Jin Hwa; Song, Jae Yun; Lee, Jae Kwan; Lee, Nak Woo
Abstract: Background: Current guidelines recommend initial colposcopy with biopsy regardless of human papillomavirus (HPV) test results in women with atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesion (ASC-H). The purpose of this study was to evaluate the value of HPV testing in women with ASC-H based on colposcopic pathology results. Materials and Methods: A multicenter cross-sectional study was carried out at three academic hospitals and involved 40, 847 Korean women who underwent cervical cancer screening with cytology and HPV tests with or without subsequent colposcopic biopsies between January 2007 and December 2013. Results: ASC-H was diagnosed in 276 women (0.7%). Only 6 of 68 (8.8%) women with ASC-H who were HPV negative had cervical intraepithelial neoplasia grade ≥2 (CIN ≥2) lesions, whereas 47.4% of the women with ASC-H who were HPV positive had CIN ≥2 lesions. No cases of invasive cervical cancer were diagnosed among women with ASC-H who were HPV negative. Logistic regression analysis was performed using the group with normal Papanicolaou test results and HPV-negative status as the reference group. Women with ASC-H who were HPV positive had a significantly increased risk of CIN ≥2 lesions, whereas no significant increase was observed in patients with ASC-H and HPV-negative status. Conclusion: If the result of the HPV test was negative, the risk of CIN ≥2 lesions in Korean women with ASC-H cytology was low. Reflex HPV testing should be an option for the management of women with cytology showing ASC-H to decrease unnecessary colposcopic biopsies, which are expensive and invasive. Implications for Practice: Current American Society for Colposcopy and Cervical Pathology guidelines recommend universal colposcopy for the management of women with atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesion (ASC-H) on cytology, regardless of human papillomavirus (HPV) test results. The present study suggested that HPV cotesting in patients with ASC-H cytology can provide more detailed and useful information regarding the risk of high-grade cervical intraepithelial neoplasia (CIN) lesions and the need for further treatment. When the result of the HPV test was negative, the risk of CIN lesions of grade ≥2 in women with ASC-H cytology was low. Consequently, reflex HPV testing, rather than immediately performance of invasive and expensive colposcopy with biopsy, should be an option for the management of women with ASC-H. Abstract : Current guidelines recommend universal colposcopy for the management of women with atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesion (ASC-H) on cytology, but the present study suggested that human papillomavirus (HPV) cotesting in patients with ASC-H cytology can provide more detailed and useful information regarding the risk of high-grade cervical intraepithelial neoplasia lesions and the need for further treatment. Reflex HPV testing should be an option for the management of these patients.